THE INFLUENCE OF COMMUNITY SERVICE ADVERTISEMENT MINISTRY OF PEOPLE’S HOUSING IN TELEVISION TOWARD COMMUNITY ATTITUDES ABOUT INCREASING OIL FUEL - Angga Mustafa; Vethy Octaviani; Fera Indasari (Perkumpulan Dosen Muda (PDM) Bengkulu, 2020)
This study entitled the effect of public service announcements on the Ministry of public housing on television on people's attitudes about the rise in fuel prices. The purpose of this study was to determine whether there was an influence of ad impressions with community attitudes. This research has two variables, they are public service advertisement (x) and attitude (y). The method used in this study is a quantitative method, data collection techniques using samples from a population and using a questionnaire as a primary data collection tool. The number of samples in this study were 40 respondents consisting of 25 men with a percentage of 62.5% and 15 people with a percentage of 37.5%. And if you look at the age you get the most respondents at the age of 20-40 years with a percentage of 75%. After the data is obtained, the results of subsequent studies are analyzed which is proven by the Pearson correlation test (r). The calculation results obtained are r = 0.77 and t arithmetic = 7.44 t table = 2.021. From the results of these calculations stated there is an influence between the display of public service ads with the attitude of the community.